Do costal erosion and urban development threat loggerhead sea turtle nesting? Implications for sandy beach management - Costa, Leonardo Lopes; Bulhões, Eduardo Manuel Rosa; Caetano, João Pedro Almeida; Arueira, Vitor Figueira; de Almeida, Daniella Torres; Vieira, Tatiane Bittar; Cardoso, Leandro Jorge Telles; Zalmon, Ilana Rosental (Frontiers in Marine Science, 2023)
Nest beach selection by sea turtles at a regional scale may depend on upper shore environmental cues. Thus, the variability of sandy beach conditions, including coastal erosion rates and urban development can affect their nesting ecology. Almost half of worldwide sandy beaches are suffering from erosion and most of them are located in highly developed areas. This can lead to shore stretches with coastal squeeze and loss of habitat for beach-dependent species such as sea turtles. Understanding whether an endangered species, such as the loggerhead sea turtle Caretta caretta (Linnaeus, 1758), selects certain beaches to nest is the first step in devising mitigation strategies for human activities and climate change impacts. We predicted that the occurrence of loggerhead nests along 62 km of sandy beaches in southeastern Brazil is negatively related to higher urbanization levels and extreme erosion. A total of 731 nests of the loggerhead sea turtle were recorded in the 2022-2023 nesting season. Only 6% of those nests were found on beach sectors with severe and extreme erosion. The probability of laying a nest was negatively related to erosion rate. Also, approximately 50% of nests were found on low-urbanized beaches; thus, the higher the urbanization, the lower the probability of a turtle laying a nest. Nature-based solutions to recover the beach-dune system are recommended in order to mitigate coastal erosion where loggerheads are avoiding nesting. This should be coupled with management planning of the protected areas where nests are laid and must include nest relocation and monitoring as priority actions.